Islamic Philonthropy at Islamic Boarding School-Based Microfinance Institutions in Madura During the Covid-19 Pandemic - Fadllan, Fadllan; Haryanto, Rudy; Harisah, Harisah; Zulzila Mohd Kusrin (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2025)
The Covid-19 pandemic has caused a significant economic downturn, including in Madura, which necessitates alternative solutions to support community economic resilience, even if the impact is not substantial. This study aims to examine the role of Islamic economic instruments implemented by Islamic boarding school–based microfinance institutions in addressing economic challenges during the Covid-19 period. The research employs a mixed-method approach, combining quantitative analysis with qualitative data obtained through interviews and observations. This approach allows statistical findings to be complemented by empirical insights into the practical implementation of Islamic microfinance practices, enabling their potential replication by other institutions or communities. he findings indicate that the economic empowerment model applied is based on philanthropy from ummah to ummah, utilizing Islamic instruments such as zakat, infaq, alms, and waqf. The hypothesis testing results show that zakat has a positive and significant effect on economic improvement, with a t-value of 3.287. In contrast, infaq does not have a significant effect, while waqf and alms demonstrate negative but significant partial effects on economic conditions during the Covid-19 period. The standard error of all independent variables is below 5 percent, indicating their overall influence on the Madurese economy during the pandemic. Furthermore, the coefficient of determination (R²) is 0.718, suggesting that zakat, infaq, alms, and waqf collectively explain 71.8 percent of the variation in economic improvement, while the remaining 28.2 percent is influenced by other factors not examined in this study.